Survey of Japanese mothers of daughters eligible for human papillomavirus vaccination on attitudes about media reports of adverse events and the suspension of governmental recommendation for vaccination. Issue 12 (30th September 2015) - Egawa‐Takata, Tomomi; Ueda, Yutaka; Morimoto, Akiko; Yoshino, Kiyoshi; Kimura, Tadashi; Nishikawa, Nobumichi; Sekine, Masayuki; Horikoshi, Yorihiko; Takagi, Tetsu; Enomoto, Takayuki
Abstract: Aim: Following media reports of adverse medical events surrounding human papillomavirus (HPV) vaccination and the suspension of Japanese governmental recommendation, most adolescents have refrained from receiving the vaccine. This represents a national critical event, because the incidence of cervical cancer in Japan continues to increase. Methods: We conducted an Internet survey to investigate why Japanese adolescent girls decline, continue or discontinue their HPV vaccination, how their mothers influence their decision, and the mothers' feelings about future HPV vaccination for their daughters. One thousand mothers with daughters 10–18 years of age were recruited for our questionnaire. Results: Our results suggest that acceptance of the HPV vaccine was determined predominantly by the mother's perceptions of risk versus benefits, rather than the daughter's wishes. The mothers' knowledge of the benefits of the prophylactic HPV vaccine and their attitude toward cervical cancer screening influenced their decision whether to allow their daughter to receive future vaccinations. The tenor of survey responses of those mothers who were anti‐vaccine changed significantly to the positive in response to a proposed scenario where the governmental recommendation for the HPV vaccine was reinstated, whereas a hypothetical educational intervention sheet did not significantly change their attitude. Conclusions: Promotion of the HPV vaccine through comprehensive education for both mothers and daughters, not only on the vaccine itself, but also about cervical cancer and screening, is required for any successful program to prevent cervical cancer.